PhI(OTf)2 Does Not Exist (Yet). Issue 68 (29th October 2020) - Tania,; Houston, Sevan D.; Sharp‐Bucknall, Lachlan; Poynder, Tiffany B.; Albayer, Mohammad; Dutton, Jason L.
Abstract: PhI(OTf)2 has been used for the past 30 years as a strong I(III) oxidant for organic and inorganic transformations. It has been reported to be generated in situ from the reactions of either PhI(OAc)2 or PhI=O with two equivalents of trimethylsilyl trifluoromethanesulfonate (TMS‐OTf). In this report it is shown that neither of these reactions generate a solution with spectroscopic data consistent with PhI(OTf)2, with supporting theoretical calculations, and thus this compound should not be invoked as the species acting as the oxidant for transformations that have been associated with its use. Abstract : Does it exist? PhI(OTf)2 has been invoked as an intermediate in I(III) mediated oxidations. In this Communication we show that the methods proposed to generate PhI(OTf)2 do not give solutions spectroscopically consistent with this species.